Maxillary first molar with two palatal roots: a case report - Salapoor M; Farhad Mollashahi N (Tehran University of Medical Sciences, 2010)
"n The goal of each root canal therapy is cleaning and obturating the entire root canal system. A thorough knowledge of root and root canal morphology and a good anticipation of their possible morphologic variations are essential and will help to reduce endodontic failure caused by incomplete root canal preparation and obturation. In this study, one case of maxillary molar with two palatal roots has been reported in a 40-year-old moman.